STUDY OFSOIL STABILIZATIONIN PALANGKARAYAUSINGWASTE GYPSUM ON ROAD PAVEMENT (SUBGRADE) - Jonlie Jonlie (Lambung Mangkurat University Press, 2015)
Subgrade is one important component in road constrctions, roads sometimes have to go through a condition where the carrying capacity of the foundation soil does not meet the requirements. Subgrade under study is a soft clay soil that has a low carrying capacity. Some improvement methods for subgrade bearing capacity has been investigated to improve the physical properties and mechanical of the foundation soil. One improvement methods is the basic soil stabilization method. Subgrade stabilization in this study uses gypsum waste where great potential of gypsum waste is expected to have added value for improving the carrying capacity of the subgrade.The percentages of waste gypsum designin this study were 2%, 6% and 10%, against the soft clay soil dry weight. This study performed physical and mechanical testing before and after stabilized mainlyon testing the carrying capacity of the method of CBR. Imaging methods with X-Ray Fluerence (XRF) was also performed onnative soil, ora mixtureof gypsum waste stabilization.The results of research showed that the addition of gypsum waste by 2%, 6% and 10%, of the dry weight of soft clay soil does not have a significant influence on the increase in the carrying capacity of the land base. The XRF method didnot find new compounds with a mixture of soil stabilization results gypsum waste.